Love, Clancy : diary of a good dog - Cameron, W. Bruce (Forge, Tor Publishing Group, 2023)
"From the internationally bestselling author of A Dog's Purpose and A Dog's Way Home comes Love, Clancy: Diary of a Good Dog, a deeply moving story with a brand-new cast of characters, including one very good dog. You've probably never met someone like Clancy. He's keeping a diary, he's falling in love, there are rivals for his affections, he lives with his best friend and his worst enemy - even taken together, these factors are maybe not that unusual, except that Clancy is a dog. His point of view is therefore perhaps...different. Told in Cameron's signature style, a tremendous cast of wonderful characters find themselves jointly and separately navigating the challenges of life, of love, and...other pets, including Clancy's "worst enemy" - one very disdainful cat. It's a lot to keep track of, especially when things start to spin hilariously out of control, but fortunately, we've got the observations of Clancy, a very good dog, who shares a valuable perspective on what is really important"--